Evaluation Method of the Gas Hydrate and Free Gas System and Its Application in the Shenhu Area, South China Sea - Pibo Su; Tingwei Li; Shurong Liang; Jinqiang Liang; Xiaoxue Wang; Xiaoming Wan; Feifei Wang; Fang Liu (Geofluids)
As a new alternative energy source, gas hydrate has attracted wide attention all over the world. Since gas hydrate is always associated with free gas, the evaluation of the gas hydrate and free gas system is an important aspect of hydrate reservoir exploration and development. In this study, based on identifying gas hydrate and free gas by well logging, the seismic reflection characteristics of gas hydrate and free gas are determined by an accurate well-to-seismic calibration method. On account of seismic reflection characteristics, AVO attributes are used to identify gas hydrate and free gas qualitatively. Using prestack and poststack inversion to get the ratio of P-wave impedance and P-wave-to-S-wave velocities, we determine the three-dimensional space distribution of gas hydrate and free gas, predict their effective porosity and saturation, and eventually achieve the meticulous depiction of gas hydrate and free gas in the body, which is necessary in subsequent estimation of gas hydrate and free gas resources. Results show that according to logging interpretation, gas hydrate of the B-well is located in the depth range of 1460–1510 mbsl and free gas is in 1510–1542 mbsl. Moreover, gas hydrate of the A-well is located in the depth range of 1425–1512 mbsl, and no obvious free gas is identified. Gas hydrate is located above free gas and distributed continuously. In plane form, gas hydrate and free gas both present subelliptical distribution in the NW-SE direction. Gas hydrate has an effective porosity of 0.30–0.40, an average saturation of 0.33–0.40, and an effective thickness of 3.0–10.5 m, whereas free gas possesses an effective porosity of 0.35–0.40, a saturation of 0.24–0.32, and an effective thickness of 2.0–5.0 m.